Treatment of angiosarcoma with pazopanib and paclitaxel: results of the EVA (Evaluation of Votrient® in Angiosarcoma) phase II trial of the German Interdisciplinary Sarcoma Group (GISG-06) - Pink, Daniel; Andreou, Dimosthenis; Bauer, Sebastian; Brodowicz, Thomas; Kasper, Bernd; Reichardt, Peter; Richter, Stephan; Lindner, Lars; Szkandera, Joanna; Grünwald, Viktor; Kebenko, Maxim; Kirchner, Marietta; et al. (Cancers, 2021)
We aimed to evaluate the efficacy and toxicity of paclitaxel combined with pazopanib in advanced angiosarcoma (AS). The primary end point was progression-free survival (PFS) rate at six months (PFSR6). Planned accrual was 44 patients in order to detect a PFSR6 of >55%, with an interim futility analysis of the first 14 patients. The study did not meet its predetermined interim target of 6/14 patients progression-free at 6 months. At the time of this finding, 26 patients had been enrolled between July 2014 and April 2016, resulting in an overrunning of 12 patients. After a median follow-up of 9.5 (IQR 7.7-15.4) months, PFSR6 amounted to 46%. Two patients had a complete and seven patients a partial response. Patients with superficial AS had a significantly higher PFSR6 (61% vs. 13%, p = 0.0247) and PFS (11.3 vs. 2.7 months, p < 0.0001) compared to patients with visceral AS. The median overall survival in the entire cohort was 21.6 months. A total of 10 drug-related serious adverse effects were reported in 5 patients, including a fatal hepatic failure. Although our study did not meet its primary endpoint, the median PFS of 11.6 months in patients with superficial AS appears to be promising. Taking recent reports into consideration, future studies should evaluate the safety and efficacy of VEGFR and immune checkpoint inhibitors with or without paclitaxel in a randomized, multiarm setting.
Gesehen am 11.05.2021